Technological Innovation in Arabic Language Education as a Tool for Community Empowerment Toward Social, Economic, and Environmental Sustainability - Mahdir Muhammad; Indah Chairun Nisa; Rizki Julia Utama (Bansigom Na Publisher, 2025)
This paper examines the transformative role of technological innovation in Arabic language education as a strategic means of community empowerment. It investigates how integrating educational technologies within Arabic teaching contributes to broader sustainable development goals (SDGs), particularly in fostering social inclusion, economic opportunity, and environmental consciousness. Employing a qualitative literature-based methodology, the study synthesizes recent advancements in mobile learning, AI-assisted platforms, and paperless educational tools. Findings suggest that when adapted with cultural sensitivity and sustainability objectives, Arabic language technologies can drive inclusive development and support marginalized communities. Recommendations are offered for educators, policymakers, and developers aiming to enhance the impact of Arabic language education in the digital age.